Implementation of Good Governance Principles in Educational Financial Management - YAQIN, Mohammad Nurul; SHALEH, Shaleh (Integration: Journal Of Social Sciences And Culture, 2024)
Purpose:Education plays a crucial role in the development of a country, and transparent and accountable management of education finance is a major factor in improving the quality and equity of education. This study aims to analyze the application of good governance principles in the management of education finance and identify the challenges faced and strategies to overcome them.Methodology:The method used is a literature study with a descriptive qualitative approach, which examines various sources, including scientific journals, books, and related regulations.Findings:The results of the study indicate that although the principles of good governance, such as transparency, accountability, participation, effectiveness, and fairness, have begun to be applied in the management of education finance, their implementation still faces various obstacles. The main challenges include limited access to financial information for stakeholders, less than optimal effectiveness of financial reporting, and low community involvement in supervision. In addition, the allocation of the education budget still does not fully pay attention to aspects of equity and fairness.Implication:To overcome these problems, this study recommends increasing the capacity of human resources in financial management, strengthening the monitoring and evaluation system, and implementing a more integrated financial management information system. With support from various parties, it is hoped that the governance of education finance can run more transparently, accountably, and effectively, so that it has a positive impact on improving the quality of education in Indonesia.